Asymmetric and Symmetric Dimethylarginines as Renal Function Parameters in Paediatric Kidney Diseases: A Literature Review from 2003 to 2022 - Michalina Jezierska; Joanna Stefanowicz (MDPI AG, 2022)
Asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA), inhibitors of nitric oxide synthase, play important roles in many processes in the body. Most data in the literature concern their importance in adult chronic kidney disease (CKD). According to them, SDMA well reflects the glomerular filtration rate (GFR), and higher ADMA concentrations are associated with hypertension and higher mortality. In addition, both substances are recognised cardiovascular risk factors in CKD. The purpose of this review was to summarise the studies on dimethylarginines in renal diseases in children, about which we have much fewer data. The review focuses specifically on dimethylarginine's relation to routinely used renal function parameters. Finally, we analysed 21 of the 55 articles published between 2003 and 2022 on dimethylarginines in kidney diseases in children (from birth to 18 years of age), obtained by searching PubMed/MEDLINE (search terms: "dimethylarginine" and "kidney").